Characterization of ZnO–TiO2 and zinc titanate nanoparticles synthesized by hydrothermal process - Jirapong Arin (2018)
© 2016, Springer Science+Business Media Dordrecht. Solutions containing zinc nitrate hexahydrate (Zn(NO 3 ) 2 ·6H 2 O) and potassium titanium oxalate dihydrate (C 4 K 2 O 9 Ti·2H 2 O) with different molar ratios of Zn:Ti at a pH of 10 were hydrothermally processed at 120, 160, and 200 °C to form ZnO–anatase, ZnO–anatase–rutile and ZnO–rutile nanocomposites. Upon subsequent calcination the precursors at high temperatures, ZnTiO 3 , Zn 2 TiO 4 , and Zn 2 Ti 3 O 8 nanoparticles were synthesized. X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), selected area electron diffraction (SAED), Fourier transform infrared (FTIR) spectroscopy, Raman spectrophotometry, and photoluminescence (PL) spectroscopy revealed the existence of nanocomposites and nanoparticles with strong emission at 386 nm for Zn 2 TiO 4 and Zn 2 Ti 3 O 8 and at 370 nm for ZnTiO 3 .